An Evaluation of the Concept of Historicism and Reality in Historical Novels - Kavaz, Ibrahim (Ahmet Yesevi Univ, 2012)
Historical sources and documents bring an important dimension to art objects. Researchers of history analyze the past from different aspects and perspectives. Narrative texts, which come into existence as art, make use of historical sources. The way the past is represented constitutes one of the significant subjects of fictional works. These works, which appear in the form of novels and which have factual historical events and characters as their subject matter, are defined as historical novels. Such novels transfer the past to the present time by representing historical information and documents and allowing us to make sense of the past from today's perspective. This study discusses the relationship between historical works and novels according to different viewpoints concerning reality. In addition, it points out how historians are similar to novelists in the way they interpret events or circumstances belonging to various periods according to their own subjective perspective.
Tarihselcilik anlayışı ve tarihî romanlarda gerçeklik üzerine bir de?erlendirme
Keywords: Historical document; objective history; historical novel; historicism; time; reality; fictive text; plotline